Pharmacokinetics, Safety and Pharmacokinetics/Pharmacodynamics Analysis of Omadacycline in Chinese Healthy Subjects - Yang, Haijing; Huang, Zhiwei; Chen, Yuancheng; Zhu, Yusong; Cao, Guoying; Wang, Jingjing; Guo, Yan; Yu, Jicheng; Wu, Jufang; Liu, Lichuan; Deng, Jun; Liu, Jing; et al. (Frontiers in Pharmacology, 2022)
Abstract Objective: Omadacycline is a new type of aminomethylcycline antibiotic, having a broad antibacterial spectrum. But the pharmacokinetic characteristics and safety profile in Chinese population remain unknown. It is also unclear whether the US approved treatment regimen is applicable for the Chinese population. Methods: In a randomized, double-blinded, placebo-controlled dose-escalated trial, the pharmacokinetics of omadacycline was evaluated by non-compartmental and compartmental model. Monte Carlo simulations were performed using the pharmacokinetic data from Chinese population to evaluate the probability of target attainment (PTA) and cumulative fraction of response (CFR) of the US FDA approved dose regimen. Results: The three-compartment model successfully described the rapid distribution and slow elimination of omadacycline after the intravenous infusion (i.v.). The double-peak concentration-time curve of the oral absorption (p.o.) was explained by the two-compartment model with two absorption compartments. The steady-state AUC of 100 mg omadacycline i.v. and 300 mg omadacycline p.o. were 12.1 and 19.4 mg•h/L, respectively. Pharmacokinetics/pharmacodynamics (PK/PD) analysis showed that the omadacycline dosing regimen with loading dose (200 mg i.v. q24h, 100 mg i.v. q12h, 450 mg p.o. q24h ×2 days or 300 mg p.o. q12h) and maintenance dose (100 mg i.v. q24h or 300 mg p.o. q24h) could cover the main pathogens of the indications acute bacterial skin and skin structure infections (ABSSSI) and community-acquired bacterial pneumonia (CABP): Staphylococcus aureus and Streptococcus pneumoniae. Also, omadacycline had showed a good safety profile in Chinese population. Conclusions: With the evidence provided, omadacycline could be a novel treatment option to Chinese patients with ABSSSI and CABP.